Development of a Self-Screening Education Model for Household Contacts of Patients with Pulmonary Tuberculosis - Abbasiah, Abbasiah; Kalsum, Ummi; Muhammad, Damris; Huda, Nizlel; Asrial, Asrial (Jurnal Kesmas Jambi, 2025)
The prevalence of tuberculosis (TB) in Indonesia continues to increase every year, placing Indonesia second in the world in terms of the number of TB cases. Efforts by the government to control TB are still hampered, one of which is the difficulty of detecting suspected TB cases due to negative stigma that makes patients reluctant to disclose their condition. This is due to a lack of knowledge. This study aims to develop a website-based educational model, “KECAPI,” enabling household contacts of TB patients to conduct self-assessments of transmission risk anytime and anywhere. The study was a development research (Research and Development) using a mixed-method approach within the ADDIE framework. The study subjects include 3 individuals in a one-on-one test, 15 persons in a small group test, and 35 persons for the field test and a control group of 35 persons. User satisfaction with the educational model was assessed using the System Usability Scale, and knowledge improvement was analyzed using the Mann-Whitney test. The “KECAPI” educational model (Recognize-Record-Check) was developed based on the Health Belief Model, Trans Theoretical Model, and Technological Acceptance Model, and was proven to be effective, easy to use, and improved household contacts' knowledge about TB. This model presents animated videos, text, and images and can be accessed via the link https://s.id/kecapitb. It is hoped that this model can be utilized by health institutions to detect suspected of TB cases in the community, thereby increasing the case detection rate and ensuring prompt and appropriate treatment.